2013
DOI: 10.3389/fnhum.2013.00416
|View full text |Cite
|
Sign up to set email alerts
|

The Ascending Reticular Activating System from Pontine Reticular Formation to the Thalamus in the Human Brain

Abstract: Introduction: Action of the ascending reticular activating system (ARAS) on the cerebral cortex is responsible for achievement of consciousness. In this study, we attempted to reconstruct the lower single component of the ARAS from the reticular formation (RF) to the thalamus in the normal human brain using diffusion tensor imaging (DTI).Methods: Twenty six normal healthy subjects were recruited for this study. A 1.5-T scanner was used for scanning of diffusion tensor images, and the lower single component of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
113
0
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(122 citation statements)
references
References 29 publications
2
113
0
7
Order By: Relevance
“…8,[37][38][39][40][41] Since the introduction of DTI, several studies have reported on the lower portion of the ARAS in healthy subjects and patients with brain injury. 5,6,12,13 In 2012, Edlow et al 6 reconstructed the ARAS connecting the brain stem to the thalamus, hypothalamus, and the basal forebrain in healthy subjects. In 2013, Yeo et al 5 reported a method for reconstruction of the lower portion of the ARAS from the pontine reticular formation to the thalamus in healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…8,[37][38][39][40][41] Since the introduction of DTI, several studies have reported on the lower portion of the ARAS in healthy subjects and patients with brain injury. 5,6,12,13 In 2012, Edlow et al 6 reconstructed the ARAS connecting the brain stem to the thalamus, hypothalamus, and the basal forebrain in healthy subjects. In 2013, Yeo et al 5 reported a method for reconstruction of the lower portion of the ARAS from the pontine reticular formation to the thalamus in healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
“…4 Human consciousness consists of arousal and awareness, which is accomplished by action of the pathway known as the ascending reticular activating system (ARAS). [5][6][7] The ARAS is a complex neural network connecting from the reticular formation of the brain stem to the cerebral cortex via excitatory relays in the intralaminar nuclei of the thalamus; therefore, accurate assessment of the ARAS plays an important role in the diagnosis and management of patients with impaired consciousness. [5][6][7][8] Successful evaluation of the ARAS has been limited despite many attempts by using conventional MR imaging, functional neuroimaging, electrophysiologic assessments, MR spectroscopy, and positron-emission tomography.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…We have assembled articles from a number of scientists who have made important contributions to this evolving field, and continue to shape it. The articles have been divided into a functional (Brooks et al, 2013;Henderson and Macefield, 2013;Ress and Chandrasekaran, 2013;Ritter et al, 2013) and a structural section (Deistung et al, 2013;Ford et al, 2013;Lambert et al, 2013;Yeo et al, 2013;Singleton et al, 2014).The functional section starts with a review by Brooks et al The wealth of methods and applications covered by the authors indicates that functional and structural brainstem-MRI methods have developed to a point where they can be applied to study of a wide range of neuroscientific problems. It is the hope of the editors that the brainstem will soon lose its label of a terra incognita and become a region of major interest in the neuroscience community.…”
mentioning
confidence: 99%